Mapping Climate Change Education in Primary Schools: A Bibliometric Analysis of Research Trends and Thematic Evolution - Bramianto Setiawan; Septian Mukhlis; Vina Iasha (PT. Intelektiva Global Nusantara, 2026)
Climate change education at the primary school level has gained increasing scholarly attention in recent years; however, a systematic mapping of its research landscape remains limited. This study aims to analyze publication trends, scientific contributions, thematic structures, and the evolution of research topics in climate change education in primary schools. A bibliometric approach was employed using data retrieved from the Scopus database covering the period 2012–2025. The search was conducted using specific keywords related to climate change, education, and primary schools, followed by a PRISMA-based selection process. Data were analyzed using Microsoft Excel for descriptive statistics, VOSviewer for keyword co-occurrence and network visualization, and Biblioshiny for collaboration and thematic mapping analysis. The findings indicate a significant growth in publications after 2020, with contributions dominated by European and English-speaking countries, although participation from Asia and Africa has increased. Thematic analysis reveals a shift from studies focusing on physical and health impacts toward more pedagogical and participatory approaches, including environmental citizenship and students’ emotional engagement. Overall, the field demonstrates a transition toward a more holistic orientation that positions primary schools as strategic spaces for strengthening climate literacy and sustainability competencies.